Translation Method of Students' Narrative Text from English Into Indonesian at SMP Swasta Ben's Group Buntu Bayu Hatonduhan - Sianturi, Oktavianti; Purba, Rudiarman; Purba, Christian Neni; Damanik, Bernieke Anggita Ristia (Innovative: Journal Of Social Science Research, 2024)
This research aims to found out the students’ translation method of students’ used translating narrative text from English Into Indonesian.This research described the kinds of translation method that used by students at grade nine in SMP SWASTA Ben’s Group Buntu Bayu Hatonduhan in translating activity. This research used qualitative method to describe the result of analysis kinds students used translation method in translating narrative text. To collect the data, the researcher used the students document study as the instrument to get the result of translation toward given text to the students. Furthermore, the students translated the text based on their comprehension. The subject of this research was twenty students at grade nine in SMP SWASTA Ben’s Group Buntu Bayu Hatonduhan. The findings of this research showed that there are some methods that students’ used in translating process. They are Literal Translation, Faithful Translation, Adaptation translation, Free Translation, Idiomatic Translation, Communicative Translation. In fact, the students’ used one until four methods in translate text. From the result of research, the researcher found that the students used six kinds in translating narrative text. They are literal, faithful, adaptation, free, idiomatic and communicative translation. As a result, Communicative Translation kind was mostly used by the students’ and none of students’ translated the text by using word for word, and semantic translation.